Hypertension and orthostatic hypotension in the elderly: a challenging balance - Julia Wiersinga; Sofie Jansen; Mike J.L. Peters; Hanneke F.M. Rhodius-Meester; Marijke C. Trappenburg; Jurgen A.H.R. Claassen; Majon Muller (The Lancet Regional Health. Europe)
Summary: Hypertension and orthostatic hypotension (OH) frequently coexist in the older population, both stemming from impaired blood pressure (BP) regulation. Managing hypertension in patients with OH presents a significant clinical challenge, particularly in frail older adults who are also prone to falls. Hypertension treatment is often suboptimal in this population due to concerns over the potential increased risk of falls associated with treatment. However, current clinical guidelines provide limited guidance on managing this complex issue. This review explores the pathophysiology of hypertension and OH, reviews existing guidelines, and examines the evidence surrounding hypertension management in patients with OH. Additionally, we provide an overview of research focused on frail older adults and offer expert-opinion-based recommendations for the management of hypertension and OH in routine clinical practice.